Rapamycin Eyedrops Increased CD4+Foxp3+ Cells and Prevented Goblet Cell Loss in the Aged Ocular Surface (2020)
ABSTRACT: Inflammation and oxidative stress accompany aging. This study investigated the interplay between oxidative stress and inflammation in the lacrimal gland. C57BL/6 mice were used at 2 to 3, 12, and 24 months of age. Nuclear factor erythroid derived-2-related factor 2 (Nrf2)-/- and corresponding wild-type mice were used at 2 to 3 and 12 to 13 months of age. A separate group of 15.5 to 17 months of age C57BL/6 mice received a diet containing an Nrf2 inducer (Oltipraz) for 8 weeks. Aged C57BL/6 lacrimal glands showed significantly greater lymphocytic infiltration, higher levels of MHC II, IFN-γ, IL-1β, TNF-α, and cathepsin S (Ctss) mRNA transcripts, and greater nitrotyrosine and 4-hydroxynonenal protein. Young Nrf2-/- mice showed an increase in IL-1β, IFN-γ, MHC II, and Ctss mRNA transcripts compared with young wild-type mice and greater age-related changes at 12 to 13 months of age. Oltipraz diet significantly decreased nitrotyrosine and 4-hydroxynonenal and decreased the expression of IL-1β and TNF-α mRNA transcripts, while decreasing the frequency of CD45+CD4+ cells in lacrimal glands and significantly increasing conjunctival goblet cell density compared with a standard diet. The findings provide novel insight into the development of chronic, low-grade inflammation and oxidative stress in age-related dry eye. New therapies targeting oxidative stress pathways will be valuable in treating age-related dry eye.